TAJAM DENGAR PETUGAS GROUND HANDLING AKIBAT TINGKAT KEBISINGAN DI BANDARA NGURAH RAI BALI - Nyoman Surayasa; I Made Tapayasa; I Wayan Putrayadnya (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2017)
ABSTRACT Noise that occurs at Ngurah Rai Airport can cause hearing loss. The purpose of this research is to know hearing loss of the staff in the airfield, relationship between hearing loss and the characteristics of the respondents (working period and use of personal protective equipment), and to know the difference of hearing loss in the engineering division and the administration department at Ngurah Rai Airport. The cross sectional method was used to analys data, 44 samples are collected randomly. Data were collected by interview using questionnaires. Results showed that 16.7% of administrative staff has hearing loss, while 83.3% were normal. In the engineering division, 60.5% has hearing loss and 39.5% has normal. Based on staff with a working period of â‰¤ 20 years, 37.5% has hearing loss and 62.5% has normal. Based on staff with a working life of> 20 years, 77.3% has hearing loss and 22.7% has normal. Based on staff who often use ear protection, 66.7% of hearing is normal and 33.3% is not normal. Based staff who did not use ear protection, 5.9% of hearing is normal and 94.1% is not normal. Keyword: planning, labor costs, construction projects